2002
DOI: 10.4049/jimmunol.168.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: IL-10-Producing CD4+ T Cells Mediate Tumor Rejection

Abstract: IL-10 has potent immunosuppressive properties, and IL-10-producing CD4+ Tr1 cells have been characterized as regulators of Th1-mediated immunity. In this study, using a s.c. model of glioma cell growth in mice, we demonstrate that CD4+, but not CD8+, T cells play a critical role in tumor rejection following vaccination with irradiated glioma cells. Surprisingly, glioma-specific CD4+ T cells produce IL-10 but neither IL-4 nor IFN-γ, and glioma rejection is compromised in IL-10−/− hosts. Hence, our findings demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 32 publications
3
42
3
Order By: Relevance
“…Both CD4 ϩ and CD8 ϩ T cells have been described to be important for the induction of tumor regression and the development of protective immunity (17,18,37,38). At first glance, the finding that CD8 ϩ , but not CD4 ϩ , T cells are required for the anti-tumor response of IL-21 is not in agreement with the doctrine that CD4 ϩ T helper cells are required for activation of naive CD8 ϩ T cells (39).…”
Section: Discussioncontrasting
confidence: 43%
“…Both CD4 ϩ and CD8 ϩ T cells have been described to be important for the induction of tumor regression and the development of protective immunity (17,18,37,38). At first glance, the finding that CD8 ϩ , but not CD4 ϩ , T cells are required for the anti-tumor response of IL-21 is not in agreement with the doctrine that CD4 ϩ T helper cells are required for activation of naive CD8 ϩ T cells (39).…”
Section: Discussioncontrasting
confidence: 43%
“…For instance, tumor-infiltrating cells such as eosinophils and macrophages contribute to an effective antitumor response after activation by neighboring tumor-specific CD4 ϩ T cells (29)(30)(31)(32). We showed that vaccine-induced CD4 ϩ T cells were capable of producing the cytolytic molecule perforin and, accordingly, may have an immediate effector function against tumors, as has been shown in vitro (33,34) and in vivo (35). Finally, IFN-␥ secreted by tumor-infiltrating CD4 ϩ T cells or activated bystander cells has the potential to promote tumor recognition and elimination by up-regulating expression of MHC molecules and might also contribute to the inhibition of tumor angiogenesis (36,37).…”
Section: Discussionmentioning
confidence: 96%
“…Recent work (Segal et al, 2002) demonstrated that IL-10 producing CD4+ T cells can manifest anti-tumor functions. The IL-10 maintains the number of anti-tumor CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%